Short-Term and Lifelong Exercise Training Lowers Inflammatory Mediators in Older Men - Hayes, Lawrence D.; Herbert, Peter; Sculthorpe, Nicholas F.; Grace, Fergal M. (Frontiers in Physiology, 2021)
Increased basal low-grade inflammation is observed with advancing age, which is augmented by physical inactivity. However, data regarding the influence of lifelong exercise training, and particularly high intensity interval training (HIIT) on inflammatory mediators in older men is scarce. Therefore, we examined effects of 6 weeks of aerobic preconditioning followed by 6 weeks of HIIT on inflammatory mediators (interleukin [IL]-6, homocysteine, and high sensitivity C-reactive protein [hsCRP]) in previously sedentary older men (SED) and masters athletes (LEX). Further, we investigated whether SED exhibited greater basal inflammatory biomarkers compared to LEX. Twenty-two men (aged 62 ± 2 years) participated in the SED group whilst 17 age-matched LEX men (aged 60 ± 5 years) also participated as a positive comparison group. In SED, preconditioning (P=0.030, d=0.34), and HIIT (P=0.030, d=0.48) caused a reduction in IL-6 compared to enrollment. SED homocysteine did not change throughout (P>0.57; d<0.26), whilst the decrease in hsCRP after preconditioning (P=0.486, d=0.25) and after HIIT (P=0.781, d=0.23) compared to enrollment was small. HIIT did not influence IL-6 or hsCRP in LEX (all P>0.42; d<0.3). Homocysteine increased from enrollment to post-HIIT in LEX (P=0.144, d=0.83), but all other perturbations were trivial. IL-6 and hsCRP were greater in SED than LEX throughout the investigation (all P<0.029; d>0.72), but homocysteine was not different (all P>0.131; d<0.41). Results of this study suggest moderate intensity aerobic exercise and HIIT lowers IL-6 (and possible hsCRP) in previously sedentary older men. Moreover, lifelong exercise is associated with reduced concentrations of some inflammatory biomarkers in older males, and therefore physical activity, rather than age per se is implicated in chronic low-grade inflammation. Moreover, physical inactivity induced inflammation may be partly salvaged by short term exercise training.